Forms and age at circumcision: some psychological implications for women's fertility (1994)
The paper attempts to examine the forms and age at circumcision with the goal of highlighting the psychological implication of the procedure for women's fertility. The findings are a product of a survey involving a randomly selected sample of 214 women conducted in two local government areas (Okpe and Sapele) of Delta state in Nigeria. The results revealed that circumcised women experience some degree of fear and anxiety states because of the practice and this has some implications for women's sexual behaviour. It also revealed that the period of recovery from the operation also tends to affect the mental image of women and by extension sexual relationships. Arising from the observed adverse effects, the paper concludes by calling for the eradication of the practice in our society.